2018
DOI: 10.1007/s00262-018-2194-0
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of PD-L1 blockade with a potency-matched dual cytokine–antibody fusion protein leads to cancer eradication in BALB/c-derived tumors but not in other mouse strains

Abstract: We have recently described a novel therapeutic antibody product (IL2-F8-TNF), featuring the simultaneous fusion of murine IL2 and of a TNF mutant with scFv(F8), an antibody specific to the alternatively-spliced extra domain A of fibronectin (EDA). Here, we report on the in vivo characterization of the anti-cancer activity of IL2-F8-TNF in four immunocompetent murine models of cancer, CT26, WEHI-164, F9 teratocarcinoma and Lewis lung carcinoma (LLC), using the product alone or in combination with a monoclonal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 66 publications
2
31
0
Order By: Relevance
“…IL2-and TNF-based products have shown to be synergistically active against various type of malignancies (4,6,8,(22)(23)(24)(25)27,42) by two distinct complementary mechanism of actions. On one hand, TNF is capable of inducing hemorrhagic necrosis and apoptosis of the tumor endothelial cells and also of cancer cells (4,6,25,43,44).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IL2-and TNF-based products have shown to be synergistically active against various type of malignancies (4,6,8,(22)(23)(24)(25)27,42) by two distinct complementary mechanism of actions. On one hand, TNF is capable of inducing hemorrhagic necrosis and apoptosis of the tumor endothelial cells and also of cancer cells (4,6,25,43,44).…”
Section: Discussionmentioning
confidence: 99%
“…depicts a schematic representation of a fully-human fusion protein (termed IL2-XE114-TNF mut ), featuring a sequential arrangement of IL2, a scFv fragment specific to CAIX (named XE114 (31)) and TNF [Supplementary Figure 1]. The protein arrangement is reminiscent of the one previously described for the murine fusion protein IL2-F8-TNF mut (6,27) [ Supplementary Figure 2], but here we used human payloads in order to facilitate clinical translational activities. The TNF moiety was de-potentiated by a single amino acid substitution (R108A), in order to achieve a similar cytokine activity for both IL2 and TNF moieties.…”
Section: Figure 1amentioning
confidence: 99%
See 1 more Smart Citation
“…However, although we detected AH1-specific T cells in the CEA-transfected tumors using tetramer reagents [ Supplementary Figure 6], there was no apparent link to a treatment regime. We have previously shown that the targeted delivery of TNF to colorectal tumors and to other cancer types in immunocompetent mouse models potently synergizes with other therapeutic modalities, including other cytokines (e.g., IL2(43) and IL12 (44)), cancer vaccines(37) and immune checkpoint inhibitors (45). In the current manuscript, we studied the combination Sm3E-TNF with 5-FU and with oxaliplatin, as these drugs are commonly used in chemotherapeutic strategies for the treatment of patients with metastatic colorectal cancer (46).…”
Section: Preliminary Mechanistic Evaluationmentioning
confidence: 99%
“…TNF is a homo-trimeric pro-inflammatory cytokine, mainly produced by macrophages, NK and T cells [10,11]. TNF is involved in inflammatory processes and as indicated by its name, it may display a potent anticancer activity against some malignancies, by promoting hemorrhagic necrosis and by inducing direct apoptosis of tumor cells [12][13][14][15][16][17]. Moreover, TNF may activate the immune system as a result of the increased inflammation [18][19][20].…”
Section: Introductionmentioning
confidence: 99%